TİCARET ŞİRKETLERİNİN TÜR DEĞİŞTİRMESİ - (:unkn) unknown (My University, 2015)
6102 sayılı Türk Ticaret Kanununda önemli değişiklikler getiren düzenlemelerden birisi de ticaret şirketlerinin tür (nevi) değişikliğidir. Kanunda 180-190 hükümleri arasında düzenlenmiş olan tür değiştirme eski Ticaret Kanununda yer alan ilkelere yer vermekle birlikte daha ayrıntılı ve yenilikçi düzenlemeler içermektedir. Yeni Ticaret Kanunu büyük ölçüde İsviçre Birleşme Kanunu ve ilgili Avrupa Birliği yönergesine dayanmaktadır. Bu çalışmada ticaret şirketlerinin tür değiştirmesine ilişkin yeni hükümlerin uygulanma alanı, kapsam ve sınırları, çeşitli sorunlara ağırlık verilmek suretiyle incelenmiştir.

An important revision in Turkish Commercial Code No. 6102 is the one related to the regulations on conversion of the type of commercial companies. Besides keeping the basic principles that were enacted in the former commercial code, the new regulations on conversion of the type of commercial companies, which take place in the articles 180 through 190 of the new code, is more detailed and innovative. The new Turkish Commercial Code is mostly based upon the Swiss Federal Act on Merger and the related European Union Directive. The area of practice, the scope and the restraints of the new regulations on conversion of the type of commercial companies are examined in this study with an emphasis on various problems encountered.
(CONVERSION OF THE TYPE OF COMMERCIAL COMPANIES)
Keywords: Hukuk